2009
DOI: 10.1140/epjc/s10052-009-1207-8
|View full text |Cite
|
Sign up to set email alerts
|

Cerenkov emission as a positive tag of double beta decays in bolometric experiments

Abstract: Active background reduction in high resolution calorimeters is a promising approach to achieve ultimate sensitivity in neutrinoless double beta decay experiments. We propose Cerenkov emission from beta rays in bolometric crystals as a viable alternative to scintillation. This novel approach could broaden the range of materials of interest for calorimetric searches of the double beta decay. We discuss the optical properties of TeO 2 crystals, as a show case.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
81
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(83 citation statements)
references
References 16 publications
2
81
0
Order By: Relevance
“…A very important issue for these instruments is the light-detector sensitivity, which is crucial to achieve an adeguate background rejection in the most challenging situation (dark matter application and detection of Cherenkov light in TeO 2 bolometers [1]), but important also for the ZnSe [2] and ZnMoO 4 [3] scintillating bolometers, which are relevant for double beta decay search. In this work, we refer to the bolometric light detectors that use high impedance neutron transmutation doped (NTD) Ge thermistors as temperature sensors.…”
Section: Introductionmentioning
confidence: 99%
“…A very important issue for these instruments is the light-detector sensitivity, which is crucial to achieve an adeguate background rejection in the most challenging situation (dark matter application and detection of Cherenkov light in TeO 2 bolometers [1]), but important also for the ZnSe [2] and ZnMoO 4 [3] scintillating bolometers, which are relevant for double beta decay search. In this work, we refer to the bolometric light detectors that use high impedance neutron transmutation doped (NTD) Ge thermistors as temperature sensors.…”
Section: Introductionmentioning
confidence: 99%
“…The signal produced by 130 Te 0νβ β decay is expected to produce a light signal of about 300 eV 8 . In literature, various Cherenkov light measurements with TeO 2 crystals can be found; the measured light signals in the ROI are always smaller than the expected ones.…”
Section: Cherenkov Light Emission In Teo 2 Crystalsmentioning
confidence: 99%
“…To this end, additional detection channels are needed, since the absorber does not respond differently for energy releases of different particle types. To distinguish signal electrons from α background, light emission can be used, either from Cherenkov radiation [22,23] or scintillation light [24,25,28,29], where the auxiliary light detector is usually another bolometer facing the main one. Recently new studies on scintillating bolometers showed the possibility to distinguish α from β/γ particles without light readout thanks to a different time-dependent shape of the heat signal [30,31].…”
Section: Beyond Cuorementioning
confidence: 99%